STRATEGI PROMOSI EKOWISATA TAMAN NASIONAL TESSO NILO PADA BALAI TAMAN NASIONAL TESSO NILO KABUPATEN PELALAWAN DALAM MENINGKATKAN WISATAWAN - Yanti, Nur; Firdaus, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Tesso Nilo National Ecotourism Park is one of potential tourist attractions in Indonesia which located in Pelalawan District and offers us a concept of forest tourism, because Tesso Nilo is a wonderful lowland tropical forest. This research aims to find out the promotional strategy which runs by Tesso Nilo National Ecotourism Park in increasing the tourists.This research was carried out in Tesso Nilo National Ecotourism Park. Using decriptive qualitative method and purposive technic where the author giving the descriptions about ecotourism research clearly and systematically. This research also uses interviews, observations, and documentations in collecting data.Based on the research, the promotional strategy which used by Teso Nilo national ecotourism park in increasing the number of tourists are; promotion mix, is an advertising promotion including outdoor media and print media; public relations, such as counseling to the surround communities, social services, and build a good relationship with the stakeholders; word of mouth, which came from the tourist’s experiences and good services especially who’ve followed the Simaksi; Personal selling, such as events and exhibitions.